The Role of Business Education in Restructuring the Funding of TVET for Sustainable Economic Recovery in Nigeria - Lukman, Suleiman; Adam, Saidu Mansur; Jibrin, Dahiru Usman; Umar, Buba (American International Journal of Social Science Research, 2017)
Over the years different researches have made emphasis on funding TVET, however this research is ambitious on finding the roles played by business education in restructuring the funding of TVET for sustainable economic recovery, in doing that, the concept of business education was discuss by different school of thought, the current status of TVET in the Nigerian context was also explain on how the acquisition of formal technical education is possible from secondary to tertiary levels of the country’s 9-3-4 education system.The legacy of under-funding from the past brought the need for providing the policy for restructuring the funding of TVET in the Nigerian system of education. Business education played an important roles in reframing the funding of TVET where ten (10) roles have been pointed out in the research means for restructuring the funding of TVET programme for sustainable economic recovery in Nigeria.